2011
DOI: 10.1002/j.0022-0337.2011.75.11.tb05209.x
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Five‐Step Method for Teaching Clinical Skills to Students in a Dental College in India

Abstract: This study conducted at the PDM Dental College and Research Institute, Haryana, India, had the purpose of developing a teaching method based upon a five-step method for teaching clinical skills to students proposed by the American College of Surgeons. This five-step teaching method was used to place fissure sealants as an initial procedure by dental students in clinics. The sealant retention was used as an objective evaluation of the skill learnt by the students. The sealant retention was 92 percent at six-and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…A literature review regarding the 5-step method found that it had the positive effects of improving performance ability and reducing the time needed to learn skills when it was applied to skill education for dental care students [16]. Teaching materials for peritoneal dialysis patients and their caregivers have been developed on the basis of the 5-step method and are expected to make peritoneal dialysis safer and more efficient for the patients when a nurse, who is the educator, uses these materials 3 [1].…”
Section: Need For Studymentioning
confidence: 99%
See 1 more Smart Citation
“…A literature review regarding the 5-step method found that it had the positive effects of improving performance ability and reducing the time needed to learn skills when it was applied to skill education for dental care students [16]. Teaching materials for peritoneal dialysis patients and their caregivers have been developed on the basis of the 5-step method and are expected to make peritoneal dialysis safer and more efficient for the patients when a nurse, who is the educator, uses these materials 3 [1].…”
Section: Need For Studymentioning
confidence: 99%
“…This study was approved by the Institutional Review Board of E University in D city (** [16][17]. For ethical protection of the participants, they were provided an explanation of the research goals, methods, and confidentiality, and those willing to participate in the study were asked to provide informed consent before the study was conducted.…”
Section: Data Collectionmentioning
confidence: 99%
“…The efficacy of using different step-bystep instructional models to teach psychomotor skills is subject of ongoing debate. When using the five-step George and Doto model or the Walker and Peyton four-step model, simple skill acquisition was significantly enhanced in studies [30,31]. In contrast, other studies comparing different skill teaching models identified no significant differences in cases of complex skill acquisition [2,10,16,22].…”
Section: Discussionmentioning
confidence: 83%
“…In brief the STEPS technique is a 5 step approach including setting the foundation, the tutor demonstrating skill without explanation, the tutor providing explanation while repeating the skill, the learner practicing under supervision and receiving feedback and then later the learner practicing independently. The SIS-FR approach is devised for structuring non-technical skills, including setting the context, immersing in roles and practicing, intervening for summary, feedback and refining practice according to feedback (17).…”
Section: Discussionmentioning
confidence: 99%